STUDY OF THE EFFICIENCY OF THE APPLICATION OF BIOGAS INSTALLATIONS AT ENTERPRISES OF THE AGRICULTURAL COMPLEX - BABENKO, Oleksiy; KUTINA, Maryna; PROTSENKO, Lyudmila (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The issue of energy saving is becoming more and more urgent, taking into account the destruction of power generating facilities. One of the energy saving options is the use of alternative energy sources. This is not only an economic benefit for consumers, but also a reduction in the load on electrical networks and maintenance of the reliability of the power system due to the decentralization of electricity generation in wartime conditions. Alternative sources of electricity include energy from the sun, wind, seas, rivers, biomass, and Earth’s heat. At the same time, their effectiveness depends on many factors. Since Ukraine has a powerful industrial agricultural complex, its share in GDP is about 10% and its share is growing annually, therefore, an urgent task is to analyze the feasibility of using biogas plants at livestock, agro-processing and municipal waste enterprises. We should not forget about the environmental friendliness of electricity production using biogas plants, which will ensure the preservation of the environment, and therefore the health of descendants. Enterprises of the agro-industrial complex for the production of products require significant amounts of electrical energy, along with this, the waste of the activities of such enterprises is sewage and organic waste in landfills, from which biomass can be obtained. Biomass, in turn, is the raw material for the production of biogas, which is needed by biogas plants to generate electrical energy. Analysis of the amount of waste from agro-industrial complex enterprises, which can be used as raw materials for the production of biogas, showed that Ukraine has prospects for the development of biogas energy, based on a powerful agricultural sector. The use of biogas plants will provide electricity, heat and hot water to enterprises of the agrarian complex, and will reduce the load on traditional energy sources.